تخفيض زمن الوصول إلى ملفات الصور باستخدام طريقة الفهرسة الشجرية المحسنة B+ Tree - ساعي, مريم; أبو قاسم, كندة; إسماعيل, أسامة (Latakia University Journal -Engineering Sciences Series, 2016)
The Research suggests a novel model aims to reduce the time of search for image files by proposing a new indexing mechanism to avoid the plague algorithm used with indexing so that the access time to these files becomes as less as possible. The first stage in this paper is to clarify the importance of archiving in organizing files via designing a database, storing images in it and recording the times needed to obtain the required files from the database. Then the indexing process for image files stored in the database is applied by proposing a new algorithm -B+ Tree enhanced- for organizing image files according to a certain mechanism to facilitate accessing any file, conducting queries and recording the times used to get those files from the database to compare them with the times required to access files before indexing in order to show the efficiency of the proposed method.يقترح البحث نظاماً جديداً يهدف إلى تخفيض زمن البحث عن ملفات الصور images عن طريق اقتراح آلية فهرسة جديدة تعالج العيوب التي عانت منها خوارزميات الفهرسة المستخدمة بحيث يصبح زمن الوصول لهذه الملفات أقل ما يمكن. تم بدايةً في هذه الورقة توضيح أهمية الأرشفة Archiving في تنظيم الملفات عن طريق تصميم قاعدة بيانات Database وتخزين ملفات الصور فيها وتسجيل الأزمنة اللازمة للحصول على الملفات المطلوبة من قاعدة البيانات, بعد ذلك تم إجراء عملية الفهرسة Indexing لملفات الصور المخزنة في قاعدة البيانات عن طريق اقتراح خوارزمية جديدة - B+ Tree المحسنة - تهدف إلى تنظيم ملفات الصور وفق آلية معينة تسهل الوصول للملفات المطلوبة وتم إجراء عمليات الاستعلامqueries وتسجيل الأزمنة المستغرقة من أجل مقارنتها مع الأزمنة اللازمة للوصول إلى الملفات قبل الفهرسة بهدف إظهار كفاءة الطريقة المقترحة.